(untitled) (TAJ: Journal of Teachers Association, 2019)
Background: Failed hypospadias refers to any hypospadias repair that leads to complicationsor causes patient dissatisfaction. One of the commonest major complications of hypospadias surgery is urethrocutaneous fistula. Objectives: Present study aimed to determine a better procedure of salvage urethroplasty for failed hypospadias, caused by persistentlarge (>4mm) or multiple -small (<4mm) fistulae, by a randomized comparison. Patients and Methods. This interventional study was performed in the department of Paediatric Surgery, Rajshahi Medical College Hospital, Rajshahi, Bangladesh, over a period of five years (from July 2011 to June, 2016). A total of 189 patients were included in present study and randomized in the three groups under study. Comparisons were made among three procedures of salvage urethroplasty of failed hypospadias caused by urethrocutaneous fistula using substitution of dorsal skin flap, Flip flap, or buccal mucosal graft in a controlled situation. Outcomes were assessed by means of objective scoring system. Results: Refistula rate, devascularization of flap and grafts and wound dehiscence rate were significantly less in Buccal mucosal graft (group A) than flip flap(group C) and dorsal transposition flap (group B ). This led to a higher success rate and better patient compliance in buccal mucosal graft. The objective scoring evaluation revealed that score gain of BM group (182) was significantly higher than that of dorsal transposition flap (112) and flip flap (89) at P value <0.05 . Conclusion: Staged redo urethroplasty for large or multiple-small fistulae using substitution of buccal mucosal graft revealed as an better option for urethral reconstruction than dorsal transposition flap and flip flap procedures (group A˃ group B ˃group C). TAJ 2018; 31(1): 38-45